PERTUMBUHAN DAN PRODUKSI TANAMAN TUMPANGSARI CABAI DENGAN BAWANG MERAH MELALUI PENGATURAN JARAK TANAM DAN PEMUPUKAN NPK PADA TANAH GAMBUT - Raisa Baharuddin; Selvia Sutriana (DINAMIKA PERTANIAN, 2019)
ABSTRACT The increased productivity of peatlands can be done by applying an intercropping system. The commodities that can be intercropped are chili and shallots. This research aims to determine the planting distance and dosage of NPK fertilization on production in intercropping of chili and shallot on peat soil. This research was conducted from August to December 2018 at the Experimental Farm, Faculty of Agriculture, and Islamic University of Riau. Research experiments used a completely randomized design with three replications. The first factor of the spacing consisted of 4 levels, J1 (50 x 50 cm), J2 (60 x 50 cm), J3 (70 x 50 cm). The second factor of NPK 16:16:16 fertilizer dosage were N0 (0 kg. ha-1), N1 (250 kg. ha-1), N2 (500 kg. ha-1), N3 (750 kg. ha-1). Shallot was planted 2 weeks before planting chili with a spacing of 20 cm x 20 cm. The results indicated that the best planting distance and dosage of NPK on intercropping chili pepper and shallots in peatland was 50 x 50 cm and NPK 500 kg/ha for growth and production of shallots. The best planting distance and dosage of NPK on intercropping chili pepper and shallots in peatland was 50 x 50 cm and NPK 750 kg/ha for the production of chili pepper.